Estudo histomorfométrico da necrose em tecido hepático de ratos: terapia fotodinâmica combinada com ablação a laser e terapia fotodinâmica com o fotossensibilizador Luzitin® - Rego, Raquel Ferreira (2012)
Photodynamic Therapy (PDT) is known to be limited to applications in large volume tumours due to its limited penetration. Therefore, the PDT with the Luzitin® photossensitizer as well as a combination of PDT and laser surgery may constitute a potential to destroy bulk tumors. Thus, with the aim of proposing a minimally invasive treatment protocol involving the application of PDT for large tumors, the present study analyzed histomorphometrically necrosis resulting from both a combination of a laser ablation with PDT as PDT with the photosensitizer Luzitin® (a bacteriochloryn synthetic with greater potential for penetration into biological tissue) in livers of healthy rats. In the first study, 87 animals were divided into 2 groups: CO2 laser and diode laser. Each of these groups were subdivided into six subgroups: 1) only laser ablation, 2) administered the PS and ablated with laser, 3) only PDT (drug and ligth), 4) drug and light (PDT) followed by laser ablation, 5) ) laser ablation followed by a PDT and 6) drug, followed by laser ablation and ligth. For each subgroup, three types of photosensitization were used: topical 5- aminilevunic acid (ALA), intravenous ALA and intravenous Photogem®. Thirty hours after the different treatments, the animals were sacrificed and the livers removed for the histological and morphometric study of necrosis. The results showed that the effects of treatment were considerably improved when PDT was used in combination with laser ablation. For the group CO2 laser, the average depth of necrosis obtained showed a minimum difference between the studied conditions for the group photosensitized Photogem® and with an increased depth of necrosis after the combined procedures in comparison with the isolated techniques for the subgroups fotossensibilizados with ALA, especially treatment with PDT was performed before ablation by CO2 laser. In the diode laser group, subgroups with better performance were those in which the ablation was performed before PDT using intravenous photosensitizers and ALA topic. From these results, it is suggested that PDT and laser ablation can synergistically in the treatment of large tumors. In the second study, sixteen normal male rats were randomly divided into 4 groups with 4 animals each. Initially, all groups were intravenously photosensitizated with 2 mg/kg or 2.6 mg/kg of the drug and after 12 hours, a 1cm2 of area, in the right abdominal region, corresponding to the liver, was irradiated during 22 minutes and 13 seconds or16 minutes and 40 seconds. Groups are described following: 1) control group: photosensitized with 2mg/kg, but untreated, 2) treated group 1: irradiated with light dose of 100J/cm2 after photosensitization with 2mg/kg of 12hs and 3) treated group 2: irradiated with light dose of 70J/cm2 and photosensitized with 2mg/kg of Luzitin®, 4) treated group 3: photosensitized with 2.6 mg/kg of the drug and irradiated with light dose of 70J/cm2 Animals were sacrificed 30 hours after irradiation, except the control group, which were sacrificed 42hs after drug administration. Livers were removed and prepared for histological analysis. Moreover, macroscopic aspects of liver were observed. Results showed significantly more extensive necrosis and greater severity in treated group 1. Data suggested that, among the conditions studied, light dose suitable for PDT treatment of photosensitized tissue by Luzitin® is 100J/cm2 and that 30% of reduction in this value produces decay in PDT response, even with proportional increase of drug concentration in the organism.